Sintesis Natrium Karboksimetil Selulosa (Na.CMC) dari Selulosa Hasil Isolasi dari Batang Alang-Alang (Imperata cylindrica L.) - Megawati Megawati; Fitriyanti Jumaetri Sami; Syatriani Syatriani (Jurnal Farmasi dan Ilmu Pengobatan, 2017)
Alang-alang (Imperata cylindrica L) is a plant thatis used as fodder. This plant contain a high cellulose content 96,7%, which can be used as the manufacture of sodium carboxymethyl cellulose. The purpose of this study to synthesize the carboxymethyl cellulose from the isolation of coarse grass (Imperata cylindrica L). Na.CMC of coarse grass (Imperata cylindrica L) obtained by alkalization of cellulose with sodium hydroxide in the solvent isopropyl alcohol in submitting etherification using sodium chloro acetate. Results of qualitative testing color identification with reactant molischshowed positive resuls, analysis formed muchilagform, a o white swelling, viscocity 8Cp, pH of 6 with a purity of 95.8%, flame test Na+ are marked with a yellow flame and FTIR results showed the wave number 3442 cm-1 -OH group, 2918 cm-1 CH , 1647 cm-1 group C = O, 1265cm-1 CO group and 894 cm-1 is CH that is the Na.CMC the synthesis.